2009
DOI: 10.1021/la9015383
|View full text |Cite
|
Sign up to set email alerts
|

Ag Dendrite-Based Au/Ag Bimetallic Nanostructures with Strongly Enhanced Catalytic Activity

Abstract: Dendritic Ag/Au bimetallic nanostructures have been synthesized via a galvanic replacement reaction (GRR) of Ag dendrites in a chlorauric acid (HAuCl4) solution. After short periods of time, one obtains structures with protruding flakes; these will mature into very porous structures with little Ag left over. The morphological, compositional, and crystal structural changes involved with reaction time t were analyzed by using scanning and transmission electron microscopy (SEM and TEM, respectively), energy-dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
130
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(138 citation statements)
references
References 45 publications
7
130
1
Order By: Relevance
“…Dendritic Ag NPs have hierarchical branches and leaves as shown in Figure 1. It stands out among other nanostructures due to its large surface area and its unique interfacial structure towards adding substrate or metals, which bring its amazing application in surface-enhanced Raman scattering (SERS) [19,20], surface-enhanced fluorescence [21], super-hydrophobic [22][23][24], antibacterial [25,26], chemical sensors [27,28] and catalysis [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Dendritic Ag NPs have hierarchical branches and leaves as shown in Figure 1. It stands out among other nanostructures due to its large surface area and its unique interfacial structure towards adding substrate or metals, which bring its amazing application in surface-enhanced Raman scattering (SERS) [19,20], surface-enhanced fluorescence [21], super-hydrophobic [22][23][24], antibacterial [25,26], chemical sensors [27,28] and catalysis [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a growing interest in bimetallic hybrid NPs, since their chemical and physical properties are different from those for both the bulk metals and their monometallic NP counterparts [15][16][17][18][19][20]. Toshima et al have reported that core-shell bimetallic NPs exhibit a higher catalytic activity than the monometallic counterparts because the catalytic activity of the shell atoms can be electronically influenced by the core atoms [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Th e catalytic activity of Pd and Pd-M alloy NPs decreased in the order Pd > Pd-Cu ≈ Pd-Ni > Pd-Ag ≈ Pd-Au > Pd-Pt. Th is result is extraordinary since most of the bimetallic catalysts had an enhanced catalytic activity as compared to the monometallic catalysts reported so far [8,67,102,126].…”
Section: Polymer-stabilized Npsmentioning
confidence: 93%
“…Instead, the enhanced rate of the nanowires is due to the abundance of grain boundaries. [3,[8][9][10]126] Zeng et al [9] presented the occasional case of synthesis using the titration of Ag nanocubes with chloroauric acid (HAuCl 4 ) in an aqueous solution under refl ux to produce three diff erent types of Au-based hollow nanostructures. Th ese were nanocages (the most porous morphology with the thinnest walls), nanoboxes and partially hollow nanoboxes.…”
Section: Nps Stabilized By Surfactants Micelles and Microemulsions [75]mentioning
confidence: 99%
See 1 more Smart Citation